Procrastination and suicide proneness: A moderated-mediation model for cognitive schemas and gender. Issue 6 (2nd July 2016) - Klibert, Jeffrey; LeLeux-LaBarge, Kayla; Tarantino, Nicholas; Yancey, Thresa; Lamis, Dorian A.
ABSTRACT: This study examined the direct and indirect paths between procrastination and suicide proneness while considering gender differences. Participants included 547 undergraduates from a southeastern university. Procrastination was positively related to suicide proneness for both genders, although this relation was stronger for women. Moderated-mediation analyses with bootstrapping highlighted insufficient self-control schemas as a mediator in the relation between procrastination and suicide proneness. However, indirect pathways did not vary by gender. Results represent an extension of the Procrastination-Health Model by highlighting the contribution of cognitive factors in explaining the relation between procrastination and suicide proneness.